Family law and property law questions in connection with the state of emergency, declared in Bulgaria (13 th March 2020 – 13 th May 2020) - Petkova, Tsvetalina (Law Journal of New Bulgarian University, 2021)
The article analyzes some family law and property law questions, arising in connection with the declared state of emergency from 13.3.2020 to 13.5.2020 on the territory of the Republic of Bulgaria due to the epidemic of COVID-19. Answers are given to the following questions: can the court consider a divorce claim or an application for divorce by mutual consent during the state of emergency; whether it is possible to attain judicial protection in cases of domestic violence in the state of emergency and under what conditions; as well as whether the acquisitive prescription is suspended during that period of time.